Revision of the Aenictus minutulus species group (Hymenoptera: Formicidae: Aenictinae) from Southeast Asia - Jaitrong, Weeyawat; Hashimoto, Yoshiaki (Zootaxa, 2012)
The genus Aenictus is a diverse group of army ants in the Old World tropics and subtropics. The worker-based Aenictus piercei species group of Jaitrong and Yamane (2011) is redefined and renamed here as the Aenictus minutulus group. Aenictus piercei Wheeler et Chapman, 1930 and A. lifuiae Terayama, 1984 are removed from this group; the former is moved to the A. javanus group and the latter to the A. ceylonicus group. The Southeast Asian species of the group are revised to include six species: Aenictus changmaianus Terayama et Kubota, 1993, Aenictus sp.56 of WJT, A. minimus sp. nov., A. minutulus Terayama et Yamane, 1989, A. peguensis Emery, 1895 and A. subterraneus sp. nov. Aenictus changmaianus, A. minimus and A. peguensis are probably restricted to the seasonal forest located northward from the Isthmus of Kra, while A. minutulus, A. subterraneus and Aenictus sp.56 of WJT are obviously Sundaland species inhabiting the perhumid evergreen rainforest.